Raman spectroscopic and chemometric investigation of lipid-protein ratio contents of soybean mutants - Yılmaz, Ayberk; Kabuk, Hayrunnisa Nur; Kaygısız, Ersin; Fausto, Rui; MERİÇ, SİNAN; AYAN, ALP; ATAK, ÇİMEN; ÇELİK, ÖZGE; ILDIZ, GÜLCE ÖĞRÜÇ (My University, 2020)
Seeds belonging to fourth generation mutants (M-4) of Ataem-7 cultivar (A7) variety and S04-05 (S) breeding line salt-tolerant soybeans were investigated by Raman spectroscopy, complemented by chemometrics methods, in order to evaluate changes induced by mutations in the relative lipid-protein contents, and to find fast, efficient strategies for discrimination of the mutants and the control groups based on their Raman spectra. It was concluded that gamma irradiation caused an increase in the lipid to protein ratio of the studied Ataem-7 variety mutants, while it led to a decrease of this ratio in the investigated S04-05 breeding line mutants. These results were found to be in agreement with data obtained by reflectance spectrum analysis of the seeds in the full ultraviolet to near-infrared spectral region and suggest the possibility of developing strategies where gamma irradiation can be used as a tool to improve mutant soybean plants targeted to different applications, either enriched in proteins or in lipids. Ward's clustering and principal component analysis showed a clear discrimination between mutants and controls and, in the case of the studied S-type species, discrimination between the different mutants. The grouping scheme is also found to be in agreement with the compositional information extracted from the analysis of the lipid-protein contents of the different samples.
Keywords: Food Analysis; Food Composition; Soybean; Soybean Mutant; Raman Spectroscopy; Principal Component Analysis; PCA; Cluster Analysis; Chemometrics